PSYCHOLOGICAL LITERACY AND ITS ASSESMENT OF IN YOUTH - Fayzullayev, Mirzaodil Mirzamurodovich (Educational Research in Universal Sciences, 2023)
The boundaries of adolescence are not clearly defined, each teenager has his own individuality. Along with the concept of "adolescence", the concept of "transitional period" is also used. During this period, a teenager goes a long way in his development: through internal conflicts with himself and others, external disturbances and upheavals, he can gain a sense of identity. At this age, the child lays the foundations of conscious behavior, a general direction appears in the formation of moral ideas and social relations.